The influence of childbirth expectations on Western Australian women's perceptions of their birth experience. - Hauck, Yvonne; Fenwick, Jennifer; Downie, Jill; Butt, Janice (Elsevier, 2007)
Objectives: to explore and describe the influence of childbirth expectations on women's perception of their birthing experience and expectations for subsequent births. This was the second phase of a study, the purpose of which its purpose was to determine the childbirth expectations of a cohort of Western Australian women and ascertain factors that influenced these expectations. Design: a qualitative study which used an exploratory descriptive design. Data were collected from in-depth individual interviews. Setting: Perth, Western Australia. Participants: 20 women, 11 primiparae and nine multiparae, who between them had experienced 31 births. These women had participated in phase one when they were either pregnant or had birthed within the preceding 12 months. Phase two interviews occurred 5?6 months after phase one.Findings: the themes and sub-themes revealed in phase one of the study were supported in phase two. Although women held multiple expectations for birth, specific expectations were regarded as priority. Consequently, to perceive birth as positive, a woman had to achieve her priority expectations. Multiparae reported more positive birth experiences, having altered expectations as a result of previous experiences. Unaffirming birth experiences due to unmet expectations were more common after a first birth. Women with unfulfilled expectations subsequently adapted their expectations to be more achievable thus avoiding disappointment. Supportive behaviours of maternity health-care providers assisted women to evaluate their birth experience as positive even when expectations could not be achieved.Implications for practice: the evaluation of birth experiences as positive or negative is contingent upon achieving most, or at least the priority, childbirth expectation. Knowing a woman?s expectations assists the midwife in her advocacy role. This role in assisting women to achieve their expectations is reinforced by this research. Caregivers become even more important when expectations are not able to be realised. Behaviours that encourage involvement and participation in decision-making during birth promote feelings of control, coping and feeling supported, which ultimately are needed for women to assess their birth experience as positive. Achievable expectations, such as ?being flexible? and ?only having a healthy baby? could be regarded as a lessening of ideals. The issue of whether these changing expectations are contributing to the increasing technocratic approach to birth and the resulting devaluing of the normal birth experience requires further debate.& 2006 Elsevier Ltd. All rights reserved.